“When a Girl Says No, You Should Be Persistent Until She Says Yes”: College Students and Their Beliefs About Consent - Baldwin-White, Adrienne (Journal of interpersonal violence, 2021)
One in five college women report being sexually assaulted with 23% to 45% of men reporting attempting or completing a sexual assault while attending a university. One important concept in preventing sexual assault is consent. It is important to ensure that when students are being asked to wait for consent, they understand what consent is and the potential ways it could manifest in a sexual situation. In total, 25 female and 20 male college students participated in semistructured focus groups or interviews to gain a better understanding of their perspectives of consent and how they ensure that it has been given. Results demonstrate that college students do not have a consistent, coherent, or precise definition of consent. Participants often described consent using vague language and were only able to clearly identify verbal indicators of consent. Much of the discussion of consent centered around an individual’s ability or inability to clearly and directly communicate his or her needs. Data also show that how students communicate about consent is influenced by gender expectations. There are multiple complicating factors when determining consent, including alcohol consumption. Participants discussed not understanding how to navigate sexual encounters when one or both parties had been consuming alcohol. Results also showed that there are multiple factors that may lead women to say yes to sex they don’t want, and men to not ask for consent. For college students, consent is a complex concept—a concept they may not have a practical and useful definition of. Sexual assault prevention must take steps to provide college students with a definition of consent informed by their experiences and the reality of their sexual encounters.